Supply Chain Strategy and Service Recovery as an Antecedent of Customer Loyalty for Insurance Company - Andala Rama Putra Barusman; Tina MB Virgawenda (International Journal of Supply Chain Management, 2019)
The aims of this study is to examine the effect of switching barrier and service recovery on customer loyalty based on the supply chain strategy. Switching barrier variable consists of procedural, fincancial and relational switching cost. Meanwhile, service recovery consists of procedural justice, interactional justice and distributive justice. Research survey conducted by collecting information from respondents using a questionnaire. The sampel used in the study is individual customers in city of Bandar Lampung, Indonesia with a total of 571 respondent. Data analysis tool used is multiple regression analysis with SPSS 18.0. The results showed that the switching barrier had a positive and significant effect on customer loyalty. Service recovery has a positive and significant effect on customer loyalty. Eventually, the switching cost and service recovery simultaneously have a positive and significant effect on customer loyalty for Insurance company in city ofÂ Bandar Lampung.